Are larger organizations more efficient and strategically stronger? A cross-sectional and longitudinal research into Dutch housing corporations - Koolma, Rik; Hulst, Rudi; Montfort (Archives of Business Research, 2017)
There is only limited research on the relation between the scale of operation of organizations and their efficiency. Moreover, the research methods used are coarse. The relation between scale of operation and strategic position has not been subject of systematic research at all. In this article, a sophisticated, theory-based method is developed to assess the relation between the scale of operation of organizations and their efficiency and strategic position. The method is applied to the sector of housing corporations in the Netherlands. Although the optimal scale of operation appears to be larger for efficiency than for strategic position, housing corporations have grown far beyond both optimal scales.